2017
DOI: 10.1186/s13046-017-0536-y
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 expression is significantly associated with chemotherapy resistance and adverse prognosis in non-serous epithelial ovarian cancer patients

Abstract: BackgroundEpithelial ovarian cancer (EOC) is a spectrum of different diseases, which makes their treatment a challenge. Forkhead box M1 (FOXM1) is an oncogene aberrantly expressed in many solid cancers including serous EOC, but its role in non-serous EOCs remains undefined. We examined FOXM1 expression and its correlation to prognosis across the three major EOC subtypes, and its role in tumorigenesis and chemo-resistance in vitro.MethodsGene signatures were generated by microarray for 14 clear-cell and 26 endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 66 publications
4
53
0
Order By: Relevance
“…As a classic proliferation-associated transcription factor, FOXM1 directly or indirectly activates the expression of target genes at the transcriptional level and exhibits a spatiotemporal pattern whose dysregulation is involved in almost all hallmarks of tumor cells [ 3 , 12 ]. Increased expression of FOXM1 is observed in a variety of human cancers, such as ovarian cancer, breast cancer, prostate cancer, hepatoma, angiosarcoma, colorectal cancer, melanoma, lung cancer, and gastric cancer [ 13 21 ], which is consistent with the results obtained from the TCGA database (Fig. 2 ).…”
Section: Introductionsupporting
confidence: 89%
“…As a classic proliferation-associated transcription factor, FOXM1 directly or indirectly activates the expression of target genes at the transcriptional level and exhibits a spatiotemporal pattern whose dysregulation is involved in almost all hallmarks of tumor cells [ 3 , 12 ]. Increased expression of FOXM1 is observed in a variety of human cancers, such as ovarian cancer, breast cancer, prostate cancer, hepatoma, angiosarcoma, colorectal cancer, melanoma, lung cancer, and gastric cancer [ 13 21 ], which is consistent with the results obtained from the TCGA database (Fig. 2 ).…”
Section: Introductionsupporting
confidence: 89%
“…expression is coordinately upregulated in a sizable proportion of patients with chemoresistant recurrent HGSC (the front line therapy for these patients is carboplatin + paclitaxel). FOXM1 is reported to promote resistance to carboplatin and taxol, and we speculate that RHNO1, which promotes the DDR, might have an additional impact on this phenotype (Carr et al, 2010;Kwok et al, 2010;Nestal de Moraes et al, 2015;Tassi et al, 2017;Wang et al, 2013). In addition, ATR and CHK1 kinases have been shown to have cancer-specific synthetic lethality, suggesting that RHNO1 loss might synergize with a CHK1 inhibitor (Sanjiv et al, 2016).…”
Section: Dual Foxm1 and Rhno1 Targeting Might Sensitize Hgsc Cells Tomentioning
confidence: 86%
“…The most common oncogenic function assigned to FOXM1 is deregulation of the G2/M checkpoint to promote cellular proliferation (Costa, 2005;Laoukili et al, 2005;Wonsey and Follettie, 2005). FOXM1 also promotes HR (Khongkow et al, 2014;Maachani et al, 2016;Monteiro et al, 2013;Park et al, 2012) and chemoresistance (Carr et al, 2010;Fang et al, 2018;Kwok et al, 2010;Tassi et al, 2017;Zhao et al, 2014). Pan-cancer analyses have demonstrated increased FOXM1 expression across a variety of cancers and a robust connection to genomic instability and poor prognosis (Barger et al, 2019;Carter et al, 2006;Gentles et al, 2015;Jiang et al, 2015;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the positive feedback of FOXM1 promotes the growth and invasion of gastric cancer and that FOXM1 promotes gastric cancer progression by interacting with PVT1 [26]. FOXM1 has also been reported in non-serious epithelial ovarian carcinoma: FOXM1 was upregulated in all epithelial ovarian cancers [27]. In addition, it has been shown that the FOXM1-PSMB4 axis can play a catalytic role in the proliferation and development of cervical cancer [28].…”
Section: Discussionmentioning
confidence: 98%